2017
DOI: 10.1186/s13075-017-1381-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and dual-energy computed tomography provide different quantification of urate burden in gout: results from a cross-sectional study

Abstract: BackgroundUltrasonography (US) and dual-energy computed tomography (DECT) can assess urate burden in gout. The objective of this study was to compare the quantification of urate deposition provided by US to the one provided by DECT.MethodsPatients with a diagnosis of gout were prospectively recruited to undergo quantification of urate deposition using US and DECT. US examination for tophi and the double contour (DC) sign was performed on the knees and feet and corresponding DECT scans provided volumes of tophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…However, it is not widely available, and in addition to being expensive and involving some radiation exposure, its use is often restricted to secondary and tertiary care centres. Its diagnostic performance, with MSU crystal identification as reference test, seems comparable to US, with a potential superiority for MSU crystal deposition detection in direct comparison with US 77–80. As observed with US, sensitivity for the diagnosis of gout is influenced by the duration of the disease, being lower in the early stage of the disease 40 48–50.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is not widely available, and in addition to being expensive and involving some radiation exposure, its use is often restricted to secondary and tertiary care centres. Its diagnostic performance, with MSU crystal identification as reference test, seems comparable to US, with a potential superiority for MSU crystal deposition detection in direct comparison with US 77–80. As observed with US, sensitivity for the diagnosis of gout is influenced by the duration of the disease, being lower in the early stage of the disease 40 48–50.…”
Section: Discussionmentioning
confidence: 89%
“…Rapidly obtaining SU levels below the dissolution threshold of MSU was associated with an OR of 1.42 of incident flares in the febuxostat trials and could be related to the mobilization of the MSU burden [ 13 ]. Prevalence of the US DC sign provides a different assessment of MSU burden than the one provided with DECT [ 14 ] and does not seem to predict the risk of flares. Flare prophylaxis is known to imperfectly prevent gout flares during ULT initiation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prospective observational study included consecutive patients with a diagnosis of gout according to the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) 2015 criteria [ 17 ]. They were recruited to undergo quantification of urate deposition of the knees and feet using US and DECT [ 14 , 20 ] and were subsequently followed in outpatient visits. The study was approved by the institutional review board of the Lille Catholic Hospitals and all participants provided informed consent before inclusion into the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, reports already con rmed that high serum uric acid increased the burden of monosodium urate (MSU) deposits. [20,21] Previous studies reported that MSU deposits would lead to structural damage in corresponding organs where the MSU deposits were found. A nephrological research found that high SUA led to uric acid super saturated in the urine, and supersaturation in the urine increased monosodium urate (MSU) deposits in the kidney formed uric acid stones.…”
Section: Smooth Curve Ttingmentioning
confidence: 99%